Dryer Cabinet Modification with Heating Element - Santoso, M T; Sudarto, G; Saputra, H (Proceeding of International Joint Conference on UNESA, 2024)
The modification of a gas-powered drying machine into an electric-powered drying machine in the Food Technology laboratory of the Family Welfare Education Department Faculty of Engineering Surabaya state of University aims to make the use of tools more effective, efficient and improve the work function of the tools. Gas dryers are more energy intensive and less practical to use. Apart from that, the distribution of hot air from gas dryers is less even. Electric powered dryers use electric heating elements as heat producers and are more environmentally friendly because they do not produce gas emissions. The electric heating element used is a tubular type heating element equipped with a ceramic insulator as safety. Hot air is distributed in the drying machine by a blower placed close to the heating source. Even distribution of hot air and a stable temperature are the keys to speed in drying. This research is research and development research. The expected result of this research is that the tool can function optimally, effectively and efficiently. Drying carried out on bay leaves with a capacity of 500 gr using an electric heating temperature of 60-70 C can dry the material in less than 5 hours.